Diagnosing MERRF requires clinical and genetic evidence - Finsterer, Josef (Polish Journal of Pathology, 2020)
The interesting case about a patients with myoclonic epilepsy with ragged-red fibers (MERRF) syndrome due to the variant m.8344A>G with a heteroplasmy rate of 95% reported by Felczak et al. expands the phenotypic spectrum of MERRF syndrome. The authors reported a pituitary adenoma, calcium deposits in arterial walls, and an intra-cerebral lipoma in the corpus callosum in their patient. Shortcomings of the study are that the diagnostic criteria for MERRF were not accomplished, that the patient should be rather diagnosed as a mitochondrial, multiorgan disorder syndrome (MIMODS), that no pedigree and heteroplasmy rates in first degree relative were provided, that hormone levels were not provided despite obvious endocrinological involvement, and that no serum or cerebrospinal fluid (CSF) lactate levels were reported.